The strength characteristics and progressive failure mechanism of soft rock-coal combination samples with consideration given to interface effects - Song, Hongqiang; Zuo, Jianping; Liu, Haiyan; Zuo, Shuhao (International journal of rock mechanics and mining sciences (Oxford, England : 1997), 2021)
The coal-measure rock masses of China's Ordos Basin are mainly composed of typical soft rock with low strength, which bear loads together with the coal seams during coal mining activities. Accurately determining the mechanical behaviors of combination soft rock and coal masses can provide a basis for underground coal engineering designs. First, uniaxial compression tests were conducted on medium sandstone samples, coal samples, and coal-rock combination samples. It was observed that the peak axial strain, uniaxial compressive strength, stress-strain curve shape, and elastic modulus of the combination samples were closer to those of the coal samples, indicating that the mechanical characteristics of soft rock-coal combination samples were mainly affected by the coal. Then, using the static equilibrium and deformation continuous conditions, along with the Griffith strength criterion, the ultimate compressive strength of materials at different positions in a combination model was analyzed. The results revealed that the interface constraint effects had reduced the strength of the sandstone near the interface and improved that of the coal near the interface. The interface constraint effects were verified by comparing the generalized Poisson's ratio of materials at different positions with those of the standard coal and sandstone samples. Finally, based on the final failure modes, and the temporal characteristics of the acoustic emission (AE) count rate and peak frequency, the progressive failure mechanism of the soft rock-coal combination samples was studied. This failure process was found to be characterized by the synergistic failure of the material and structure. Furthermore, the effect of coal-rock height ratio on the strength of materials at different positions was discussed, which interpreted the experimental results observed in the previous related studies, namely, with the increase in the rock-coal height ratio, the strength of the combination samples had increased, and the impact tendency had been significantly enhanced.